Immobilized Ru‐Pincer Complexes for Continuous Gas‐Phase Low‐Temperature Methanol Reforming‐Improving the Activity by a Second Ru‐Complex and Variation of Hydroxide Additives. Issue 18 (2nd May 2021) - Schwarz, Christian H.; Kraus, Dominik; Alberico, Elisabetta; Junge, Henrik; Haumann, Marco
Abstract: Ru‐pincer complexes were immobilized as supported liquid phase (SLP) materials to allow the methanol reforming reaction as continuous gas phase process. Under reaction conditions, the liquid phase forms from the hydroxide coating. Several hydroxides were screened and CsOH showed highest activity compared to the standard KOH coating. The well‐known Ru‐pincer complex carbonylchlorohydrido [bis(2‐di‐i‐propylphosphinoethyl)amine]ruthenium(II) is limited in catalyzing the final step of the methanol reforming. Addition of a second complex, having a methylated backbone in the pincer‐ligand, could overcome these limitations. Significant enhancement of the overall catalytic activity was observed. Abstract : The steam reforming of methanol benefits from low temperatures to avoid CO formation. Ru‐pincer catalysts were immobilized in supported liquid phase of aqueous hydroxide solutions. In continuous vapor‐phase reactions the performance of such SLP catalysts was improved by 130 %.